Two new varieties of Agapetes (Ericaceae) from Xizang, China - Yi-Hua Tong; Xiang-Long Guo; Bing-Mou Wang; Zi Wang; Yong-Jie Guo (PhytoKeys)
Two new varieties from Xizang, China, i.e. Agapetes interdicta var. flaviflora and A. forrestii var. parvifolia, are described and illustrated. Agapetes interdicta var. flaviflora differs from the nominate variety in having yellow and smaller corollas with shorter lobes and anthers with shorter appendages at the base. Agapetes forrestii var. parvifolia is distinguished from the nominate variety in the smaller leaves with an acute apex, nearly transverse secondary veins and puberulent peduncle. Taxonomic notes on these taxa are also provided.